KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS MANUSKRIP KEAGAMAAN (Analisis Heremeunetik Subyektif Terhadap Serat Panitiboyo ) - AM Wibowo (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This research tries to analyze the Serat Panitiboyo in compiling the Islamic education curriculum in school. The Serat Panitiboyo is one of thousands of manuscripts in Indonesia that still exists in an effort to build the character and personality of society in order to have a strong and wise character. The focus of this research is (1) to know the values of religious education that exist in the script of Serat Panitiboyo, (2) to see whether the value of religious education available in Serat Panitiboyo is appropriate in preparing the curiculum of Islamic religious education especially in preparation of Islamic religious studies with the curriculum 2013. Using the subjective Hermineutic analysis, this study had founds two findings; (1) Manuscript of Serat Panitiboyo contains religious education guidance in marriage, ethics, cultivating an honest, simple life, modeling, building relationships with gods and people, building relationships with the natural environment, laws, immoral life restrictions, dependencies etc. (2) the value of religious education in the script of Serat Panitiboyo can be added in the preparation of Islamic Religious Education materials and the curriculum of 2013 Key words: Serat Panitiboyo, Islamic education curriculum, heremeunetic subjective analysis.